Dynamic location models of mobile sensors for travel time estimation on a freeway - Sun, Weiwei; Shen, Liang; Shao, Hu; Liu, Pengjie (Zielona Góra: Uniwersytet Zielonogórski)
Travel time estimation for freeways has attracted much attention from researchers and traffic management departments. Because of various uncertain factors, travel time on a freeway is stochastic. To obtain travel time estimates for a freeway accurately, this paper proposes two traffic sensor location models that consider minimizing the error of travel time estimation and maximizing the collected traffic flow. First, a dynamic optimal location model of the mobile sensor is proposed under the assumption that there are no traffic sensors on a freeway. Next, a dynamic optimal combinatorial model of adding mobile sensors taking account of fixed sensors on a freeway is presented.
Keywords: traffic mobile sensor; dynamic location model; travel time estimation; simulated annealing algorithm; data fusion